The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.5194/angeo-29-1179-2011
|View full text |Cite
|
Sign up to set email alerts
|

On the nature of particle energization via resonant wave-particle interaction in the inhomogeneous magnetospheric plasma

Abstract: Abstract. When a quasi-monochromatic wave propagating in an inhomogeneous magnetoplasma has sufficiently large amplitude, there exist phase-trapped resonant particles whose energy increases or decreases depending on the "sign" of inhomogeneity. The variation of energy density of such particles can greatly exceed the wave energy density which contradicts energy conservation under the prevalent assumption that the wave serves as the energy source or sink. We show that, in fact, the energy increase (or decrease) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 22 publications
1
53
0
Order By: Relevance
“…A similar question about energy sources has been previously raised for large‐amplitude whistler waves observed in the outer radiation belt [ Cattell et al , ; Cully et al , ; Kellogg et al , ; Wilson et al , ] and capable of providing fast energization of electrons trapped into the Landau or cyclotron resonances [ Trakhtengerts et al , ; Agapitov et al , , ; Osmane et al , ]. Shklyar [] has shown that whistler wave energy is insufficient to provide transport of resonant trapped electrons to 30°–40° latitude, where whistlers are still observed [ Cattell et al , ; Kellogg et al , ; Agapitov et al , ]. Shklyar [] has shown that the energization of resonant trapped electrons can be balanced by energy losses of untrapped electrons scattered by whistler waves [see also Shklyar and Matsumoto , ].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…A similar question about energy sources has been previously raised for large‐amplitude whistler waves observed in the outer radiation belt [ Cattell et al , ; Cully et al , ; Kellogg et al , ; Wilson et al , ] and capable of providing fast energization of electrons trapped into the Landau or cyclotron resonances [ Trakhtengerts et al , ; Agapitov et al , , ; Osmane et al , ]. Shklyar [] has shown that whistler wave energy is insufficient to provide transport of resonant trapped electrons to 30°–40° latitude, where whistlers are still observed [ Cattell et al , ; Kellogg et al , ; Agapitov et al , ]. Shklyar [] has shown that the energization of resonant trapped electrons can be balanced by energy losses of untrapped electrons scattered by whistler waves [see also Shklyar and Matsumoto , ].…”
Section: Introductionmentioning
confidence: 80%
“…The energy loss rate is largely provided by Landau resonant untrapped electrons. The energy loss rate of untrapped electrons per unit area is given by expression very similar to equation [ Shklyar , ; Vasko et al , ] normaldWnormalutnormaldt=normaldBnormaldtΩnormalsepμFnormalut(,vϕ,μ)normaldμ where Fnormalut(,vϕ,μ) is the distribution function of Landau resonant untrapped electrons at |z|. In fact, electrons effectively exchanging energy with EH are those within the resonance width, |vvϕ|(2eΦ0/me)1/2.…”
Section: Energization Of Trapped Electronsmentioning
confidence: 99%
“…Thus, integral operators were proposed to include them into a kinetic equation [40][41][42] to take this process into account. However, in many plasma systems with nonlinear wave-particle interaction, trapping effects are somehow compensated by effects of nonlinear scattering [35,43,44], i.e. the rapid acceleration of a small population of trapped particles corresponds to a slight energy decrease for a large population of scattered particles.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown in a number of studies that ULF waves at the boundaries of the magnetosphere are able to enhance the radial diffusion [ Elkington et al , 1999; Hudson et al , 1999, 2000, 2001]. Models that are based on the interaction of the electron population with waves [ Shklyar , 2011; Shklyar and Matsumoto , 2009; Shprits et al , 2008; Omura et al , 2007; Horne et al , 2005; Summers and Thorne , 2003; Summers et al , 1998, 2002, 2004; Albert , 2003, 2005] assume the local diffusion in the pitch angle and in the energy space. This results in the acceleration of one part of electron population and the filling of the loss cone by the subsequent precipitation of another part.…”
Section: Introductionmentioning
confidence: 99%